2007
DOI: 10.1111/j.1423-0410.2007.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of alloimmune thrombocytopenia

Abstract: A: A screening and intervention program aimed to reduce mortality and serious morbidity associated with severe neonatal alloimmune thrombocytopenia. Blood 2007; 110 :833-839 2 Ghevaert C, Campbell K, Stafford P, Metcalfe P, Casbard A, Smith GA, Allen D, Ranasinghe E, Williamson LM, Ouwehand WH: HPA-1a antibody potency and bioactivity do not predict severity of fetomaternal alloimmune thrombocytopenia. Transfusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…FNIT is a devastating disease, and effective therapeutic intervention is currently limited and unstandardized (73). We previously demonstrated that maternal IVIG infusion ameliorated neonatal thrombocytopenia in the anti-β3 FNIT model (34).…”
Section: Discussionmentioning
confidence: 99%
“…FNIT is a devastating disease, and effective therapeutic intervention is currently limited and unstandardized (73). We previously demonstrated that maternal IVIG infusion ameliorated neonatal thrombocytopenia in the anti-β3 FNIT model (34).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for fetal alloimmune thrombocytopenia include: (i) very preterm delivery at 32 weeks, accepting the risk of intracranial hemorrhage known to occur as early as 14-16 weeks' gestation; (ii) repeated maternal immunoglobulin G infusions; 25,26 (iii) repeated fetal platelet transfusions with a cumulative procedurerelated risk; and (iv) serial scans with the questionable option of late termination. 27,28 In order to assess efficacy of any treatment and to balance the risks and benefits of non-invasive and invasive approaches, the natural course of the disease should be known.…”
Section: Discussionmentioning
confidence: 99%
“…Tidligere ble føtal blodprøvekontroll (trombocyttelling) og føtale trombocyttransfusjoner utført, men dette gjøres som hovedregel ikke i dag fordi prosedyren gir stor risiko for blødningskom-plikasjoner (11). I Norge er det per i dag sjelden at moren behandles med intravenøs injeksjon av polyklonalt immunglobulin før fødselen, men vi mener det er sannsynlig at dette i fremtiden vil bli anbefalt som standardbehandling hos kvinner som tidligere har født barn med hjerneblødning indusert av føtal/neonatal alloimmun trombocytopeni.…”
Section: Figur 1 Mr Caput T2-opptak Med 15 Tesla-maskin Bildeopptaunclassified